ChemInform Abstract: A Novel Non‐Metathetic Behavior of Grubbs′ Catalyst: Ruthenium‐Mediated Intramolecular [3 + 2] Cycloaddition of Bis‐1, 3‐dienes. Issue 23 (16th May 2013) - Takagi, Ryukichi; Yamamoto, Koumei; Hiraga, Yoshikazu; Kojima, Satoshi; Abe, Manabu
Abstract The title reaction affords bicyclic products (II) and (IV) in moderate yields.